2004
DOI: 10.1016/j.devcel.2004.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Lamellipodin, an Ena/VASP Ligand, Is Implicated in the Regulation of Lamellipodial Dynamics

Abstract: Lamellipodial protrusion is regulated by Ena/VASP proteins. We identified Lamellipodin (Lpd) as an Ena/VASP binding protein. Both proteins colocalize at the tips of lamellipodia and filopodia. Lpd is recruited to EPEC and Vaccinia, pathogens that exploit the actin cytoskeleton for their own motility. Lpd contains a PH domain that binds specifically to PI(3,4)P2, an asymmetrically localized signal in chemotactic cells. Lpd's PH domain can localize to ruffles in PDGF-treated fibroblasts. Lpd overexpression incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
465
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(499 citation statements)
references
References 51 publications
31
465
1
1
Order By: Relevance
“…Activation of receptor tyrosine kinases (RTKs) such as EGFR (EGF receptor) and PDGFR (PDGF receptor) lead to PI3 kinase (PI3K)-mediated generation of D3-phosphoinositides, including PI(3,4,5)P 3 and PI(3,4)P 2 [the latter mostly through PI(3,4,5)P 3 dephosphorylation by 5′-phosphatases]. Consistent with this, PDGF stimulation has been shown to recruit lamellipodin or even the isolated PH domain of lamellipodin to the leading edge and the tips of dorsal ruffles (21,22). We found that PI3K inhibition by LY294002 dramatically inhibits lamellipodin accumulation at the leading edge in profilin1 knockdown MDA-231 cells (with or without rescue by R88L-profilin1) under PDGF-stimulated condition (Fig.…”
Section: Profilin1 Inhibits Mda-mb-231 Cell Motility By Attenuatingmentioning
confidence: 54%
See 2 more Smart Citations
“…Activation of receptor tyrosine kinases (RTKs) such as EGFR (EGF receptor) and PDGFR (PDGF receptor) lead to PI3 kinase (PI3K)-mediated generation of D3-phosphoinositides, including PI(3,4,5)P 3 and PI(3,4)P 2 [the latter mostly through PI(3,4,5)P 3 dephosphorylation by 5′-phosphatases]. Consistent with this, PDGF stimulation has been shown to recruit lamellipodin or even the isolated PH domain of lamellipodin to the leading edge and the tips of dorsal ruffles (21,22). We found that PI3K inhibition by LY294002 dramatically inhibits lamellipodin accumulation at the leading edge in profilin1 knockdown MDA-231 cells (with or without rescue by R88L-profilin1) under PDGF-stimulated condition (Fig.…”
Section: Profilin1 Inhibits Mda-mb-231 Cell Motility By Attenuatingmentioning
confidence: 54%
“…Lamellipodin, a phosphoinositide binding protein, was previously shown to play an important role in recruiting Ena/VASP to the leading edge in fibroblasts and melanoma cells (note that lamellipodin targets to the leading edge independently of Ena/ VASP) (21,22). Lamellipodin depletion by siRNA markedly reduced VASP accumulation at the leading edge in profilin1 knockdown MDA-231 cells (Fig.…”
Section: Profilin1 Inhibits Mda-mb-231 Cell Motility By Attenuatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors that are important in the network formation and maintenance are regulators of actin polymerization, such as profilin that binds and targets actin monomers to the barbed ends, therefore preventing self-nucleation and ensuring actin incorporation into the proper network, and ADF/cofilin that severs the filaments at the branch points (debranching) and promotes depolymerization from the pointed ends. In filopodia, anti-capping proteins, such as Ena-VASP and their partners (Bailly et al, 1999;Krause et al, 2004;Lafuente et al, 2004) and bundling proteins, such as fascin (Adams, 2004a;Adams, 2004b), are especially important. A large number of other actin-binding proteins participate in the leading edge actin dynamics, facilitating different stages of actin assembly, disassembly, sequestering, and crosslinking.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%
“…S1, available in the online Supplementary Material). The EVH1 domains target Ena/VASP proteins to sites of actin rearrangements via interactions with proteins containing the proline-rich motif (D/E)(F/L/W/Y)PPPPX(D/E)(D/E) (designated FPPPP), including zyxin and vinculin at focal adhesions and lamellipodin at the leading edge (Hoffman et al, 2006;Krause et al, 2004;Niebuhr et al, 1997). EVH1 domains also bind to diaphanous formin (Dia) and mammalian diaphanous formin 2 (mDia2), inhibiting actin nucleation and elongation (Barzik et al, 2014;Bilancia et al, 2014), and recent data suggest that VASP activates WAVE (Wiskott-Aldrich syndrome verprolin homology protein) via EVH1-mediated interactions (Chen et al, 2014;Havrylenko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%